THE CAPACITY OF ENERGY ABSORPTION ANALYSIS ON A BUS SUPERSTRUCTURE WITH HAZ CONCEDERED - ADIKRISHNA G (NIM : 131 06 087), ANDIKA
Until now, Indonesia does not have a safety standards for passenger vehicles such as buses. The testing for vehicles such as buses only based on the evaluation of structural strength. This final test report will discuss about the strength of the bus structure which is expressed as the energy absorption capacity of the bus rollover accident, based on ECE - R66 standard, a safety standard of the European buses. Finite element method to be used to cut the expense in conducting the rollover test according to the standard ECE-R66. Finite element method is a method of numerical procedures aimed to obtain results quickly and closer to the real condition. Finite element method is suitable to find the deformation created by the rollover of the superstructure bus. From the results of the previous analysis, it is known that failure often occurs at the Heat Affected Zone (HAZ). HAZ is the area which formed after two or more objects welded. To model the HAZ, the welding model was made and placed on each bus connection in the superstructure of the tested rollover bus. After analyzed, the part that uses the welding model has a yield stress of 3900 N and after testing, the deformation of a superstructure which use a welding model is larger. At the same deformation point with the superstructure without welding model in 8000 N load, there is a difference of 4,38% of the energy absorbed. In the subsequent analysis found that the superstructure bus is safe as it reaches the ultimate stress before it reaches the residual space (safe passenger zone).